Georgius Paulus Imhof; Reip. Nor. II. Vir Prim. Præt. Et Castellan Nec Non Summ. Ærar. & Xenodoch. Ad Sp. S. Præfect. : Nat. A. MDCIII. Den. A. MDCLXXXIX. - Lang, Georg Jacob (1689)
Nürnberger Kaufmann und Ratsherr